Indigenous Peoples and the United Nations Vol. I (Awareness Raising Film) - Sommer, Rebecca (Sommer Films, 2006)
Verzio FF Submission What is to be done when land has been taken away, culture was significantly destroyed and the language is dying? When disaster strikes and atrocities are committed, the world looks at the United Nations to intervene, react and to help, but for most of its history, the doors of the UN have been closed to indigenous peoples, and for decades they were left to fend for themselves. “Indigenous Peoples and the United Nations Vol.1” is a documentary aiming to promote and raise-awareness on indigenous issues within the UN system, among politicians and diplomats. It was commissioned by the Secretariat of the United Nations Permanent Forum on Indigenous Issues (UNPFII) in 2006. The result is an eye-opening documentary about the pressing issues faced by indigenous people around the world.